Possibilities of introduction of electronic trade under conditions of meat processing enterprises - Одарченко, Андрій Миколайович; Сподар, Катерина Вікторівна; Соколова, Євгенія Борисівна (Technology audit and production reserves, 2015)
The article examined with aspects of practical application of wide variety of forms, methods and means of e-commerce in a particular company. The aim of the study was to evaluate the current state of e-commerce in Ukraine. Ways to implement e-commerce on the investigated meat processing Kharkov Ltd. "PIK and K". As the results of the researches it is found that Web-site of the company "PIK and K" is not only a way to send messages to potential customers, but also complement the advertising campaign, which provides the opportunity for feedback and interactive work with the company. It was found that the Internet-shop (e-mail, virtual, e-shop) is one of the most popular e-commerce business models in the field of B2C, designed to promote consumer products on the market, increase sales, attract new customers. Requirements for online store are analyzed and aspects of its development and implementation in a meat processing plant are identified. Thus, the use of modern innovative means of electronic commerce by enterprises will strengthen the market position and increase profits. The presented results of the research are promising in terms of increasing knowledge on the practical implementation of innovative methods of trade in the food industry in Ukraine.